1999
DOI: 10.1103/physrevd.61.024005
|View full text |Cite
|
Sign up to set email alerts
|

Signature of chaos in gravitational waves from a spinning particle

Abstract: A spinning test particle around a Schwarzschild black hole shows a chaotic behavior, if its spin is larger than a critical value. We discuss whether or not some peculiar signature of chaos appears in the gravitational waves emitted from such a system. Calculating the emitted gravitational waves by use of the quadrupole formula, we find that the energy emission rate of gravitational waves for a chaotic orbit is about 10 times larger than that for a circular orbit, but the same enhancement is also obtained by a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 31 publications
2
52
0
Order By: Relevance
“…Getting a better detailed sense of how the M酶ller radius appears due to this perturbation approach may become useful for understanding the precise conditions for a transition into chaotic dynamics, as suggested in previous work [18][19][20][21].…”
Section: Kinematic and Dynamical Quantitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Getting a better detailed sense of how the M酶ller radius appears due to this perturbation approach may become useful for understanding the precise conditions for a transition into chaotic dynamics, as suggested in previous work [18][19][20][21].…”
Section: Kinematic and Dynamical Quantitiesmentioning
confidence: 99%
“…In particular, the MPD equations lend themselves well to numerical analysis with applications involving gravitational wave generation in a Kerr background [16,17], evidence of deterministic chaos within particle orbital dynamics [18][19][20][21], and particle motion in a Vaidya background with radially infalling radiation [22]. Recently, a first-order perturbative analysis of the MPD equations was developed by Chicone, Mashhoon, and Punsly (CMP) [23], who applied their formalism to the study of rotating plasma clumps in astrophysical jets.…”
mentioning
confidence: 99%
“…In the previous work [17,18], the parameter region for a spinning test particle in which a particle will show chaotic behavior was discussed. We adopt such parameters, e.g.…”
Section: A Spinning Particlementioning
confidence: 99%
“…It is also important to study chaos in general relativity because the Einstein equations are nonlinear. Many authors have reported chaos in general relativity [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23]. As for a realistic astrophysical object, there has been a discussion whether or not chaos occurs in a compact binary system [21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of spinning test particles which are close to massive compact objects was investigated by several authors; this kind of investigation includes, generation of gravitational waves as spinning particles fall into black holes [20,21,22], chaotic behavior of spinning particles in certain space times [23,24,25] and numerical computations for orbital motions in Kerr background [26]. Interesting results regarding the interaction of spinning test matter with gravitational and electromagnetic waves have been obtained by studying the classical motion of the spinning test particles in plane gravitational and electromagnetic field solution to the Einstein-Maxwell equations [27].…”
Section: Introductionmentioning
confidence: 99%